Artikel Hubungan Peran Keluarga dengan Kepatuhan Minum Obat pada Anggota Keluarga dengan Hipertensi di UPTD Puskesmas Menteng Palangka Raya” - Rendy Orlando; Henry Wiyono; Angga Arsesiana (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Hypertension or high blood pressure is a medical condition that can cause serious complications, such as stroke and heart disease. The causes of hypertension are very diverse, ranging from unhealthy diet, lack of physical activity, stress, to genetic factors. The phenomenon that occurs at the UPTD Menteng Palangka Raya Health Center, namely that there are still many families who have not carried out their role as the right family members and have not been able to overcome family health problems, for example, such as compliance with taking hypertension medication in family members who suffer from hypertension. The purpose of this study is to determine the relationship between family roles and medication adherence in family members with hypertension. This type of research is correlational using a cross-sectional  approach using a spearman rank statistical test. The sampling technique used in consecutive sampling at the Menteng Palangka Raya Health Center. Sampling in this study is based on the inclusion criteria set. Data collection in this study used questionnaires on family roles and medication adherence that had gone through validity and reliability tests with Cronbach's alpa for family role 0.89 and Cronbach's alpa for medication adherence 0.92. Based on statistical tests using  Spearman's rank , a correlation coefficient value of 0.812 with a significance value of <0.001 was obtained. It can be concluded that there is a significant relationship between the role of the family and medication compliance at the Menteng Palangka Raya Health Center. The relationship between family roles and medication adherence in family members with hypertension at the Menteng Palangka Raya Health Center.”